Meningkatkan Pemahaman Peserta Didik Dalam Pembelajaran PAI Dengan Menggunakan Metode Cooperative (Teams,Games,Turnament) di SMPN 1 Karawang Barat - Muhamad Reza Febrian; Naira Dwiyanti Syahrudin; Isna Lokahita; Nur Aini Farida; M. Makbul (Najah Bestari, 2024)
This research aims to increase students' active participation in PAI learning using a cooperative team games tournament (TGT) type method. TGT cooperative learning is a learning model that allows students to learn and work in small groups in a collaborative and diverse group environment. This type of research is PTK (Classroom Action Research). PTK is carried out in 2 cycles. The PTK stages include the teacher identifying problems to plan action, implementing it, observing the results, and reflecting on it to continue to improve learning in the classroom. As a result, in the second cycle (II) the active participation of individual students increased to 30 people with a percentage of 92.5%. This shows the difference in the increase in cycles 1 and 2, namely 41%, so this percentage can be said to mean that almost all students have been able to show that their participation process has become active in learning. Based on the PTK that was implemented in cycles 1 and 2, it can be concluded that the researchers succeeded in implementing the Team Games Tournament (TGT) cooperative learning model in PAI subjects. This model makes lessons interesting and fun, and attracts students to participate actively.